2006
DOI: 10.1002/mds.20764
|View full text |Cite
|
Sign up to set email alerts
|

Rasagiline improves quality of life in patients with early Parkinson's disease

Abstract: The objective of this study was to determine the effects of rasagiline as monotherapy on quality of life (QOL) in patients with early Parkinson's disease (PD). Rasagiline, a potent, second-generation, irreversible, selective monoamine oxidase B inhibitor improves PD symptoms in patients with early PD. Patients with early untreated PD were randomly assigned to once-daily rasagiline 1 mg/day, rasagiline 2 mg/day, or placebo in a 6-month, double-blind trial (n=404). At the end of 6 months, patients entered the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
38
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(43 citation statements)
references
References 20 publications
3
38
0
2
Order By: Relevance
“…The PDQ-39 and PDQL are generally accepted as valid HRQoL measures for PD [11,15,40,41] and have therefore been included as a variable of interest or outcome in clinical research [5][6][7][8][9][10]. To our knowledge, however, there is no study that has sought to compare the psychometric attributes of these scales when simultaneously applied to the same population.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…The PDQ-39 and PDQL are generally accepted as valid HRQoL measures for PD [11,15,40,41] and have therefore been included as a variable of interest or outcome in clinical research [5][6][7][8][9][10]. To our knowledge, however, there is no study that has sought to compare the psychometric attributes of these scales when simultaneously applied to the same population.…”
Section: Discussionmentioning
confidence: 97%
“…In PD, HRQoL has been studied from different standpoints [1,2,[4][5][6] and is frequently included as a primary or secondary end point in clinical trials [7][8][9][10]. At least eight PD-specific HRQoL measures have been developed since 1995 [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…brainÀderived neurotrophic factor (BDNF)), bioenergetics (coenzyme Q10) and the novel antiÀParkinson drug rasagiline (Azilect1; NÀpropar-gylÀ1(R)Àaminoindan), a second generation selective inhibitor of monoamine oxidase (MAOÀB) [3,4]. Rasagiline is a promising new drug for PD in light of lately reported benefits in PD patients with early illness [5,6]. Recent multiÀcenter doubleÀblind monoÀtherapy with rasagiline by the Parkinson Study Group [5] and as adjunct therapy to LÀDOPA [7] have shown that rasagiline confers significant symptomatic improvement.…”
Section: Introductionmentioning
confidence: 99%
“…In a placebo-controlled study in early PD (ref. 12 ), rasagiline monotherapy resulted in a significant improvement in self-image/sexuality domain subscore and global QoL measured on the PD-QUALIF. In our study in PD patients with FoG on add-on therapy with rasagiline, we observed an improvement in global PDQ-39 score and the scores of three subscales, with a particularly marked improvement for the mobility subscale.…”
Section: Discussionmentioning
confidence: 96%